Justiça fiscal no âmbito do contencioso administrativo tributário do Estado do Ceará: uma avaliação de resultados - Nogueira, Elizabeth Regina Marinho Espínola (2013)
The policy of fiscal justice offered by the State through the Administrative Litigation tributary of the State of Ceará (CONAT/CE), component part of Ministry of Finance of the State of Ceará (SEFAZ/CE), constitutes an additional guarantee for the solution of tax have. The existence of such a body for the state of Ceará is a step forward for the people of Ceará, because founds a democratic State governed by the rule of law for the protection and guarantee of fundamental rights, where the taxpayer can discuss the fiscal requirement imposed upon it. For the state, this component allows the exercise of the principle of selfcontrol of public administration, where the State to revise their own acts, maculados of errors, defects or illegality. It was an assessment in the field of investigative policy of fiscal justice and the axis of evaluation a policy of harmonisation of social relations between the tax authorities and taxpayers in the realisation of the ideal of justice. The discussion was focused on discussing: in the light of the constitutional principles in force, and the theories of justice and citizenship, public policies implemented by the Ministry of Finance of the State of Ceará, through the CONAT/CE allows an understanding of the role of the Treasury with the rights of the taxpayer in obtaining tax justice? The proposal of this field avaliativo had as finality valued the politics of Fiscal Justice in the context of the Contentious Administrative Tributary of the State of the Ceará. Regarding the specific objectives it is inserted: a) to value like the contentious of the State of the Ceará conceives the fiscal justice, by means of indicators of justice chosen inside the Theory of Justice of John Rawls; b) to value if the fiscal justice in the context of the CONAT/CE has the essential configuration of tax revenue for the State of the Ceará. c) to value if the acting of the CONAT/CE reaches the fiscal justice valued through interviews and internal reports on the reached results of the judgements of the cars of breach. So, in this paradigm, by means of the results of judgements occurred in the period 2008-2012, with the materialização of the perception of the interviewed ones inside the perspective of the used indicators of justice and of the technique of observation participant, noted that the CONAT/CE makes possible, in part, the legitimation of the acting of the Internal Revenue Service near the society. In the perception of three methods used in this inquiry, in the qualitative and quantitative approach, in other words, you interview, straight observations and in the results of judgements of the period of 2008-2012, it was noticed that in a general way, it was confirmed that the CONAT/CE legitimizes, in part, the fiscal justice near the Taxpayer and near the society, when realization of skills, lawyers' absence was excepted in the perspectives of little in some of the assisted sessions and taxpayers of enterprises of small transport and small businesses that did not feel contemplated with this fiscal justice, moment in which, it is made opportune to register the necessity of a new diary of inquiries, for a qualitative approach more precise of these aspects. The tax revenue logic for the State exists and do not clash with the perspective of fiscal justice applied by the organ, so, though the consequent resolution of the tax work brings with itself the consequent tax tax revenue, it brings also the control and quality of the tax launch that is given in the CONAT/CE as it was seen in this inquiry.